2016
DOI: 10.1093/aob/mcw152
|View full text |Cite
|
Sign up to set email alerts
|

Root-mediated signal transmission of systemic acquired resistance against above-ground and below-ground pathogens

Abstract: Background and Aims Plants modulate defence signalling networks in response to various biotic stresses via inter-organ communications. The root-mediated transmission of systemic acquired resistance (SAR) against soilborne and air-borne plant pathogens from SAR-induced plants to neighbouring plants subjected to local chemical and pathogen treatments was evaluated.Methods The first two plants out of ten Nicotiana benthamiana seedlings were pre-treated with the SARtriggering chemical benzothiadiazole (BTH). All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Overexpression of CaSBP08 in transgenic N. benthamiana enhanced susceptibility to P. capsici infection, as demonstrated by the higher average disease area and disease index percentage compared to WT plants ( Figures 6B, E). Besides, the NbPR1a and NbPR1b genes, which are involved in the SA-induced systemic acquired resistance pathway and JAmediated disease resistance signaling pathway, respectively, were induced in the CaSBP08 transgenic and WT plants (Sohn et al, 2007;Cheol Song et al, 2016). PR1a and PR1b, two reported defense-related genes in tobacco, can be highly induced by tobacco mosaic virus (TMV) (van Huijsduijnen et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of CaSBP08 in transgenic N. benthamiana enhanced susceptibility to P. capsici infection, as demonstrated by the higher average disease area and disease index percentage compared to WT plants ( Figures 6B, E). Besides, the NbPR1a and NbPR1b genes, which are involved in the SA-induced systemic acquired resistance pathway and JAmediated disease resistance signaling pathway, respectively, were induced in the CaSBP08 transgenic and WT plants (Sohn et al, 2007;Cheol Song et al, 2016). PR1a and PR1b, two reported defense-related genes in tobacco, can be highly induced by tobacco mosaic virus (TMV) (van Huijsduijnen et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of the SA signaling marker gene NbPR1a was associated with systemic acquired resistance (SAR) against Pseudomonas syringae pv. tabaci (Cheol Song et al, 2016). PR1b is a JA-responsive gene in tobacco (Sohn et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…So far, leaf-derived VOCs in interplant communication have resulted in changes to aboveground physiology. Similarly, involvement of leaf-derived VOCs in intraplant communication has shown microbiome shifts and plant defense response (Song et al, 2016). There exists a gap in our knowledge of how VOCs may modulate interplant communication by changing belowground plasticity and root–microbe interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that aboveground pathogen and herbivore attack shifts microbiome activity at the belowground level (Yang et al, 2011; Song et al, 2016). We have shown previously that plants under attack by pathogenic bacteria induce a shoot-to-root systemic signal, inducing roots to recruit benign, protective microbes (Rudrappa et al, 2008; Lakshmanan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Above- and below-ground herbivores can induce emission of root signals that can be perceived by other plants. As a result, stimulated systemic defense response can be induced, following increased attraction of the predatory to herbivores arthropods or parasitoids (Dicke and Dijkman, 2001 ; Guerrieri et al, 2002 ; Cheol Song et al, 2016 ). Biotic stresses are not sole inducers of interplant communication, in a similar manner, it can be induced by abiotic stresses.…”
Section: Plant Communicationmentioning
confidence: 99%